Changes in the Preventive Vaccination Procedures in Children's City Outpatient's Clinic and its Efficacy - Snezhana D. Timoshkova; Dina S. Rusinova; Tatyana N. Elagina; Galina P. Glazkova; Marina V. Fedoseenko; Leyla S. Namazova-Baranova ("Paediatrician" Publishers LLC, 2023)
This article describes the implementation stages of the changes in preventive vaccination procedures in Children's City Outpatient's Clinic №133 of the Moscow Department of Health since December 2019. Comprehensive work has been performed on increasing the adherence to vaccination among doctors of various specialties, vaccination and immunization coverage of the registered pediatric population. As a result of this project medical prevention department was reorganized, data on vaccinations, medical exemption and refusals were added to the electronic medical records, monthly monitoring of vaccination coverage rate was initiated, as well as doctors training in preventive immunization via three forms of education. Center for Medical Prevention of the Moscow Department of Health, pediatric department of the Pediatric Faculty of Pirogov Russian National Research Medical University, the Union of Pediatricians of Russia have participated in this work. Intermediate results on efficacy of implemented measures have been presented.